Energy dissipation caused by impact or slow compression of dust aggregates consisting of fibers - Iwano, Shiori; Tanaka, Rena; Katsuragi, Hiroaki (Progress in earth and planetary science, 2025)
In the process of planetesimal formation, the mechanical properties of highly porous dust aggregates play a key role. However, it has not been easy to form highly porous dust aggregates in laboratory experiments. To solve this problem, we produce dust aggregates consisting of fibrous monomers. Specifically, silk fibers are entangled in the turbulent flow made by a vacuum cleaner. As a result, the solid fraction of the produced dust aggregates shows ϕ ≃ 10 - 3 for all aggregate samples. This value is much smaller than the dust aggregates consisting of grain monomers. To characterize the mechanical properties of this new type of dust aggregate, we perform a simple free-fall impact experiment on a hard floor and a static compression test, under the effect of Earth gravity. The coefficient of restitution (COR) of centimeter-scale dust aggregates with an impact velocity ( ∼ 1 m s - 1 ) is measured based on the image analysis of the impact-and-rebound movies. We find that the measured COR is almost constant, ∼ 0.1–0.2. Regarding the compression test, dust aggregates are slowly compressed up to 4–6 mN compression force and then slowly decompressed. In this cyclic compression test, the hysteretic behavior of the compression force is observed. From these two observations, we estimate the degree of energy dissipation in the deformed highly porous dust aggregates consisting of fibers. The obtained result implies that fibrous dust could be a useful model for experimentally mimicking highly porous dust aggregates. Namely, the fibrous aggregates can offer valuable insights for estimating the timescale of planetesimal formation and so on, in future studies.